Koefisien perpindahan panas volumetris dan kapasitas penyimpanan panas pada sistem penyimpan energi panas kontak langsung - Panut Mulyono (Jurnal Rekayasa Proses, 2007)
The volumetric coefficient of heat transfer and the energy storage capacity in a direct contact thermal energy storage system using Na2CO3.10H20 solution as a thermal energy storage medium have been investigated Hot kerosene was used as a heat transfer fluid The experiments were carried out by bubbling hot kerosene from the bottom of a column containing Na2CO3.10H2O solution. The column used in this experiment was made of glass of 3 mm in thickness with 7 cm of Inside diameter and 100 cm of height. A simple model to calculate the volumetric coefficient of heat transfer of the system has been developed The effects of kerosene flow rate and kerosene bubble diameter on the volumetric coefficient of heat transfer and the storing rate of energy were studied It was found that the volumetric coefficient of heat transfer was strongly affected by the flow rate of the kerosene and that the effect of the kerosene flow rate on the storing rate of energy was relatively high, while that of the effect of the bubble diameter was small. The relationship between the volumetric coefficient of heat transfer (in the form of the dimensionless group) and the kerosene bubble Reynolds number is Nu = 0.2362 Rei1.1475 with a mean relative error of 0.45% for the range of Reynolds number of 5 to 13.2.